Building Students’ Moral Through Uswatun Hasanah Principles: A Systematic Literature Review - Kandiri Kandiri; Arfandi Arfandi; Moh. Zamili; Masykuri Masykuri (FITK UIN Walisongo, 2021)
School or madrasah needs to instill good attitudes in the form of speech and behavior in daily activities. The prophet taught Muslims a good example (uswatun hasanah) for students when they gathered and interacted with different communities. Uswatun hasanah, or excellent conduct, is an Islamic religious value born from training and habitual action by providing a good example. Religious and moral education is essential as the root of forming a believer-pious person. This study seeks to understand uswatun hasanah through systematic literature by exploring knowledge patterns in the national database. The results indicate that good moral guidance (uswah) is not based on theoretical teaching but necessitates concrete examples through the role and responsibility of educators in the context of learning and learning processes. As such, educators should be an example (uswatun hasanah) (a good example) for students through excellent conduct in day-to-day activities.